Respuesta :
Answer:
3 and -5
Step-by-step explanation:
(x-3)(x+5)greater than and =0
separate
(1).
x - 3 > 0
add 3 to both sides
x > 3
(2).
x + 5 > 0
subtract 5 from both sides
x > -5
So, The solutions are 3 and -5
Answer: [tex](-\infty,-5]\ U\ [3,\infty)[/tex]
Step-by-step explanation:
Given the inequality [tex](x-3)(x+5)\geq 0[/tex], to find the solutions, we need to follow this procedure:
- First case:
[tex]x-3\geq 0[/tex] and [tex]x+5\geq 0[/tex]
Solve for the variable "x":
[tex]x\geq 0+3\\x\geq 3[/tex]
[tex]x\geq 0-5\\x\geq -5[/tex]
Then:
[tex]x\geq 3[/tex]
- Second case:
[tex]x+5\leq 0[/tex] and [tex]x-3\leq 0[/tex]
Solve for the variable "x":
[tex]x\leq 0-5\\x\leq -5[/tex]
[tex]x\leq 0+3\\x\leq 3[/tex]
Then:
[tex]x\leq-5[/tex]
Finally, the solution is:
[tex](-\infty,-5]\ U\ [3,\infty)[/tex]